Pemanfaatan Sosial media marketing Dalam membangun UMKM HR-TEA - Pasha, Alif; Lestari, Destianti; Napitu, Benward Yehezkiel; Amanda, Dhea; Khatami, Abang Azzidan; Habib Agil Munawar; Anjas Pratama; Tiara Fitari (FEB Universitas Maritim Semarang, 2024)
This research discusses the utilization of social media as a marketing strategy to increase brand awareness and competitiveness of MSMEs (Micro, Small and Medium Enterprises), with a case study of HR-TEA in Pangkalpinang. A descriptive qualitative approach was used through interviews, observations, and the implementation of digital marketing strategies, such as Instagram account creation and Google Maps registration, to expand market reach and increase interaction with customers. The results showed that digital marketing strategies involving creative content and social media optimization were able to increase branding, the number of followers, as well as consumer interaction, which overall contributed to the growth of MSMEs (Micro, Small and Medium Enterprises) in the face of market competition.